Economic motives of homo economicus location decisions in the context of shrinking cities in Poland - Wichowska, Anna (Ekonomia i Prawo. Economics and Law, 2025)
Motivation: Currently, two trends are observed in the development of cities worldwide. There is a group of cities that have been systematically growing in population and a group of cities that have been rapidly losing their inhabitants in recent years (this is the so-called process of urban shrinkage). Many factors condition decisions to leave one's city and choose another. Therefore, this article addresses the problem of identifying economic factors that may influence decisions about the choice of the place of life and work of the economic man (homo economicus – h.e.). The concept of h.e. is based on the assumption of the rationality of economic decisions (in terms of consumption and economic activity) made by the economic man. It may also allow us to understand his location decisions. This man is guided by the desire to achieve the maximum return on all his actions. Aim: The research aimed to identify factors that differentiate shrinking cities from cities that are not undergoing this process in the context of the decision of the homo economicus to change the place of residence and choose his new place of residence. Results: The conducted research shows that h.e. when deciding whether and where to leave in search of a better place to live and work, may take into account factors that differentiate shrinking cities from cities that are not experiencing a loss of inhabitants. These factors include, in particular, local investment expenditure, expenditure on education and social welfare, housing situation, city innovation manifested in the development of higher-order services, and unemployment level. The values ​​of indicators describing these features indicate a better situation of growth cities compared to shrinking cities. In shrinking cities, a worse situation may affect migration decisions h.e., while in growth cities, their favorable levels may attract h.e.